Skin Graft Care on Large Wound Defect After Necrotizing Fasciitis of The Leg - Fory Fortuna; Amanda Yulita Amalia (Scientific Journal, 2025)
Introduction:  Necrotizing fasciitis (NF) is an aggressive bacterial infection that causes extensive necrosis of subcutaneous tissue and fascia. Treatment of NF includes radical surgical debridement, often resulting in large wounds that need to be closed using split-thickness skin grafts (STSG).  However, clinicians should be fully aware of the postoperative management of patients with skin grafts due to its high risk of failure, especially in the lower limb. The success of a skin graft depends on the graft care along each step to provide the graft with the best chance of survival.  Case Illustration: A 79-year-old male with a large open wound on the left foot after debridement of an abscess 1 month ago due to necrotizing fasciitis. A skin graft was performed on the patient one day after being treated. Donor skin was taken from the left femur area and attached to the open wound area of the left cruris region. The skin graft was fixed with prolene, then covered with antibiotic ointment gauze and sterile gauze, and immobilized with a backslab. One week later, graft take and no sign of infection or graft failure. Redressing was done, and the patient was controlled again in one week. Discussion: The healing process of the graft heavily relies on vascular integration and careful management, with special attention to short-term complications. Conclusion: STSG is an effective procedure for covering large area wounds, with advantages such as lower metabolic burden for recipient and better nutrient diffusion than FTSG. However, STSG needs proper graft care, and follow-up in the success of STSG.